Implementation of benson relaxation as complementary therapy in addressing anxiety in high-risk pregnant women - Adri Idiana (Science Midwifery, 2023)
This systematic review aims to evaluate the implementation of Benson Relaxation as a complementary therapy in addressing anxiety among high-risk pregnant women. A comprehensive search was conducted in electronic databases, including PubMed, Scopus, and Cochrane Library, using predefined keywords and inclusion criteria. Studies published between [insert time frame] were included. The search identified 13 relevant articles, which were screened for eligibility. Data were extracted and synthesized to assess the effectiveness and potential benefits of Benson Relaxation in reducing anxiety levels among high-risk pregnant women. The systematic review included [number] studies that met the eligibility criteria. The findings consistently indicated that the implementation of Benson Relaxation as a complementary therapy was effective in addressing anxiety in high-risk pregnant women. The studies demonstrated significant reductions in anxiety levels among participants who received Benson Relaxation interventions. Furthermore, Benson Relaxation was associated with improved psychological well-being, decreased fear related to childbirth, enhanced mother-fetus bonding, and potentially positive childbirth outcomes. This systematic review provides compelling evidence supporting the implementation of Benson Relaxation as a complementary therapy in addressing anxiety among high-risk pregnant women. The findings suggest that Benson Relaxation can be an effective intervention for reducing anxiety levels and improving overall maternal well-being during pregnancy. Further research is needed to explore the optimal dosage, duration, and long-term effects of Benson Relaxation in this population.